One Implementation Method of Trust Evaluation Tool Used on Cloud Computing Service - Yang, Shengju (Recent Advances in Electrical & Electronic Engineering, 2019)
In order to solve the trust problems between users and cloud computing service providers in cloud computing services, the existing trust evaluation technology and access control technology in the cloud computing service are analyzed. And the evaluation index of cloud computing is also analyzed. Users can calculate the relevant indicators of cloud computing service according to their own business goals, and choose the appropriate cloud computing services according to their own trust need. In addition, the reliability assessment method of users based on the service process is proposed. Cloud computing access control system can be used for user credibility evaluation, and it can handle user access requests according to user's creditability. In the study, a cloud computing service trust evaluation tool is designed, and the modeling and architecture designs of trust evaluation are also given. The effectiveness of the method is verified by experiments on cloud computing service evaluation methods.
Keywords: method